Spectrum of Neurological Symptoms in Glycosylphosphatidylinositol Biosynthesis Defects: Systematic Review - Paprocka, Justyna; Hutny, Michał; Hofman, Jagoda; Tokarska, Agnieszka; Kłaniewska, Magdalena; Szczałuba, Krzysztof; Stembalska, Agnieszka; Jezela-Stanek, Aleksandra; Śmigiel, Robert (Frontiers in Neurology, 2022)
Background: Mutations of genes involved in the synthesis of glycosylphosphatidylinositol and glycosylphosphatidylinositol-anchored proteins lead to rare syndromes called glycosylphosphatidylinositol-anchored proteins biosynthesis defects. Alterations of their structure and function in these disorders impair often fundamental processes in cells, resulting in severe clinical image. This study aimed to provide a systematic review of GPIBD cases reports published in English-language literature. Methods: The browsing of open-access databases (PubMed, PubMed Central. and Medline) was conducted, followed by statistical analysis of gathered information concerning neurological symptomatology. The inclusion criteria were: studies on humans, age at onset (<18 y.o.), and report of GPIBD cases with adequate data on the genetic background and symptomatology. Exclusion criteria were: publication type (manuscripts, personal communication, review articles); reports of cases of GPI biosynthesis genes mutations in terms of other disorders; reports of GPIBD cases concentrating on non-neurological symptoms; or articles concentrating solely on the genetic issues of GPI biosynthesis. Risk of bias was assessed using Joanna Brigs Institute Critical Appraisal Checklists. Data synthesis was conducted using STATISTICA 13.3.721.1 (StatSoft Polska Sp. z.o.o.). Used tests were chi-square, Fisher's exact test (for differences in phenotype), and Mann-Whitney U test (for differences in onset of developmental delay). Results: Browsing returned a total of 973 articles which, after ruling out the repetitions and assessing the inclusion and exclusion criteria, led to final inclusion of 77 articles (337 GPIBD cases) in the analysis. The main outcomes were prevalence of neurological symptoms, onset and semiology of seizures and their response to treatment, and onset of developmental delay. Based on this data a synthesis of phenotypical differences between the groups of GPIBD cases and the general GPIBD cases population was made. Discussion: A synthetical analysis of neurological components in clinical image of GPIBD patients was presented. It highlights the main features of these disorders, which might be useful in clinical practice for consideration in differential diagnosis with children presenting with early-onset seizures and developmental delay. The limitation of this review is the scarcity of the specific data in some reports, concerning the semiology and onset of two main features of GPIBD.